Pore network of cement hydrates in a High Performance Concrete by 3D FIB/SEM — Implications for macroscopic fluid transport. (January 2019) - Song, Yang; Davy, C.A.; Troadec, D.; Bourbon, X.
Abstract: The pore structure of a mature industrial High Performance Concrete (HPC) is characterized at the scale of its cement hydrates with 3D Focused Ion Beam/Scanning Electron Microscopy (FIB/SEM). The considered scale is a mesoscale, with sample volumes of 61–118 μm 3, and voxel sizes of 5.9 × 7.5 × 10 nm 3 (or 5.9 × 7.5 × 20 nm 3 ). Four independent samples are imaged deliberately in the cement hydrates for minimal evaluation of pore structure fluctuations. The investigated pore sizes range between 10 and 600 nm. Katz-Thompson model derived from percolation theory, coupled to pore structure data from FIB/SEM, predict fluid transport properties in the Darcy's sense. Upscaled predictions at the mesoscale of the cement hydrates are on the same order of magnitude as experimental permeability at the pluri-centimetric scale (i.e. a macroscale for the HPC). This means that the pore network of the cement hydrates, imaged by FIB/SEM, has a relevant contribution to fluid transport through the HPC. Graphical Abstract: Highlights: Pore structure of the cement hydrates of an industrial High Performance Concrete is assessed. 3D FIB/SEM relates to four volumes of 61–118 μm 3 (mesoscale) selected in the hydrates. All volumes percolate significantly with a total porosity of 14.2 % ± 3.9. Total porosity of FIB/SEM samples represents 41% of macroscopic porosity. Katz-Thompson transport model correlates with macroscopic test data (2–4 ⋅ 10 −19  m 2 ).